2004
DOI: 10.1111/j.0042-9007.2004.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL PAPER. Relative values of the interventions of diversion and improved donor‐arm disinfection to reduce the bacterial risk from blood transfusion

Abstract: The study validates diversion and an improved donor-arm disinfection procedure. In combination, these two interventions produced a substantial reduction in contamination. These procedures are to be introduced by the English National Blood Service to enhance the safety of the blood supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 10 publications
10
101
0
3
Order By: Relevance
“…Since the risk of blood product contamination is associated with the presence of bacterial flora on donor arm which can contaminate the whole blood as soon as the blood collection is started, it is advisable to divert first few ml of blood into a separate pouch. McDonald et al [15] have reported that the effective donor arm disinfection in combination with diversion of initial volume of blood donation from the collection bag is the best approach to prevent blood bag contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Since the risk of blood product contamination is associated with the presence of bacterial flora on donor arm which can contaminate the whole blood as soon as the blood collection is started, it is advisable to divert first few ml of blood into a separate pouch. McDonald et al [15] have reported that the effective donor arm disinfection in combination with diversion of initial volume of blood donation from the collection bag is the best approach to prevent blood bag contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Special collection bags were manufactured for a study to determine the effectiveness of diversion [15]. These bags consisted of two sampling pouches attached to the standard collection bag configuration.…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…These include a specific donor history to identify asymptomatic bacteremia, appropriate skin disinfection procedures before venipuncture, initial aliquot diversion, and consistent implementation of the principles of good manufacturing practice with defined hygiene standards [2,3].…”
Section: Introductionmentioning
confidence: 99%